2006
DOI: 10.1097/01.mbp.0000200482.72410.e2
|View full text |Cite
|
Sign up to set email alerts
|

Can a simulator that regenerates physiological waveforms evaluate oscillometric non-invasive blood pressure devices?

Abstract: This represents the first evaluation of non-invasive blood pressure devices with a simulator that generates previously recorded clinical oscillometric waveforms. It allowed data from over 100 study participants to be used. Both devices had been previously clinically validated, but their evaluation using the simulator with its regenerated waveforms only partly met the required criteria. Although the results did not fully match previous clinical validations, these initial results give encouragement that a simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Validation standards and protocols allow for this range of agreements with statistical criteria for determining the acceptability of NIBP devices [14,15]. Simulator NIBP device evaluations also show good agreement for some oscillograms, but poor for others [12,13,16]. The results of a simulator evaluation of the Propaq LT [16] were re-analysed to select oscillograms associated with good and poor agreement between oscillometric and auscultatory pressure measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation standards and protocols allow for this range of agreements with statistical criteria for determining the acceptability of NIBP devices [14,15]. Simulator NIBP device evaluations also show good agreement for some oscillograms, but poor for others [12,13,16]. The results of a simulator evaluation of the Propaq LT [16] were re-analysed to select oscillograms associated with good and poor agreement between oscillometric and auscultatory pressure measurements.…”
Section: Introductionmentioning
confidence: 99%
“…One manufacturer has described differences in oscillogram shapes, suggesting a relationship between the shape and patient age and arterial hardening [11]. A simulator capable of regenerating previously recorded patient oscillograms [12] provided the opportunity to study the dependency of blood pressure measurements on the oscillogram. Previous work with the simulator suggested that the shape of the oscillogram, described by its systolic and diastolic characteristic ratios, might contribute to the differences between oscillometric and auscultatory measurements [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, further research concerning the substitution of clinical trials with waveform simulators is ongoing. In addition, new generations of waveform simulators with ''real'' physiological signals are currently in development [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…17 These simulators have the potential to be a reliable and convenient method for testing NIBP monitor validity. [27][28][29] Nonetheless, simulators are not typically used during validation procedures. Simulators offer the possibility of greatly improving testing reproducibility, especially when compared with clinical validation trials, where sphygmomanometers are used.…”
mentioning
confidence: 99%